Evaluation of granulocyte colony-stimulating factor effect on the expression of inhibitory receptors by T cells in multiple myeloma - E. V. Batorov; T. A. Aristova; V. V. Denisova; G. Yu. Ushakova (Медицинская иммунология, 2024)
All types of immune cells are involved in the pathogenesis of multiple myeloma (MM). Granulocytic (G-MDSCs) and monocytic myeloid-derived suppressor cells (M-MDSCs) have significant protumor effects. The T cell immune response may be reduced due to the development of T cell exhaustion, characterized by the expression of inhibitory receptors PD-1, TIM-3, etc. Granulocyte colony-stimulating factor (G-CSF) supports the generation and expansion of MDSCs and can influence the functional properties of T cells. The purpose of our work was to investigate the possible effect of stimulation with G-CSF drugs on the induction of PD-1 and TIM-3 expression by T cells in patients with MM. The study included 40 patients with MM who underwent mobilization of hematopoietic progenitor cells with G-CSF drugs (5 mcg/kg/day) for 4-5 days. Content of CD4+PD-1+, CD4+TIM-3+, CD8+PD-1+, CD8+TIM-3+T cells, Lin-HLA-DR-CD33+CD66b+G-MDSCs, and CD14+HLA-DR-M-MDSCs was assessed before the start of a course of G-CSF injections (n = 33), after a course of G-CSF on the first day of separation of hematopoietic progenitor cells (n = 28) and after 3-6 months (n = 40) by flow cytometry. The relative content of G-MDSCs and M-MDSCs was significantly higher in patients with MM after a course of G-CSF. After 3-6 months, the content of G-MDSCs and M-MDSCs decreased to the initial values. After the course of G-CSF, an increase in the content of CD4+PD-1+T cells was noted compared to the values before the study. After 3-6 months, the content of this population did not differ from the initial values. The relative numbers of CD4+TIM-3+, CD8+PD-1+, and CD8+TIM-3+T cells did not change after a course of G-CSF. There were no significant correlations between the content of the populations of MDSCs and T cells expressing PD-1 and TIM-3 after a course of G-CSF.Mobilization of hematopoietic stem cells by G-CSF in patients with MM is accompanied by a transient increase in MM populations and an isolated increase in CD4+PD-1+T cells.